2021
DOI: 10.3390/ijms23010072
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Mechanisms of Action of MDA-7/IL-24: A Ubiquitous Cancer-Suppressing Protein

Abstract: Melanoma differentiation associated gene-7/interleukin-24 (MDA-7/IL-24), a secreted protein of the IL-10 family, was first identified more than two decades ago as a novel gene differentially expressed in terminally differentiating human metastatic melanoma cells. MDA-7/IL-24 functions as a potent tumor suppressor exerting a diverse array of functions including the inhibition of tumor growth, invasion, angiogenesis, and metastasis, and induction of potent “bystander” antitumor activity and synergy with conventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 153 publications
0
7
0
Order By: Relevance
“…Moreover, WX8 together with AdV‐ IL24 overexpression was more than twice as effective in terminating PIKFYVE‐sensitive melanoma cells as either agent alone. Accordingly, PIKFYVE inhibitors could complement the ability of ectopically expressed IL24 to induce cancer‐specific cell death in patients with advanced cancers (discussed in [ 74 , 75 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, WX8 together with AdV‐ IL24 overexpression was more than twice as effective in terminating PIKFYVE‐sensitive melanoma cells as either agent alone. Accordingly, PIKFYVE inhibitors could complement the ability of ectopically expressed IL24 to induce cancer‐specific cell death in patients with advanced cancers (discussed in [ 74 , 75 ]).…”
Section: Discussionmentioning
confidence: 99%
“…The present study demonstrated that PAI-1 is a key molecule that supressed IL-24 expression in MLS cells. IL-24 is a unique antitumor cytokine with various tumor-suppressive activities, including the suppression of tumor growth, invasion, and metastasis (33). IL-24 regulates key proteins involved in the regulation of endoplasmic reticulum stress and mitochondrial function, and induces apoptosis with toxic autophagy in diverse malignant tumor cells (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, among the upregulated cytokine genes, IL24 exhibited the most substantial increase following GFP-MYPOP expression. IL24 encodes the well-studied tumor suppressive interleukin-24, also known as melanoma differentiation association protein-7 (MDA-7) [34][35][36][37] . Moreover, our analysis identi ed several well-characterized proto-oncogenes, such as MYC, FOS, and JUN, among the downregulated candidates (Supplementary Table 1).…”
Section: Mypop Modulates Gene Expression Of Cytokines and Cell Cycle ...mentioning
confidence: 99%
“…These cytokines play crucial roles in wound healing processes and in the tumor microenvironment (TME) 66,67 . Hereby, of particular interest is the well-studied tumor suppressor cytokine IL-24, a member of the IL-10 family also called MDA-7, which among other functions in cell differentiation, host defense, and wound healing 68,69 was shown to induce apoptosis in tumor cells, as demonstrated in a phase I clinical trial 34,37,70 . This implies that MYPOP blocks multiple steps of the cell cycle by silencing oncogenes, modulating cell cycle regulators and induction of IL-24, which might collectively contribute to the inhibition of cell growth.…”
Section: Mypop's Impact On Gene Expression Of Cell Cycle Regulatorsmentioning
confidence: 99%